PENGARUH TINGKAT KECERDASAN DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI MAHASISWA PROGRAM STUDI AKUNTANSI DI UNIVERSITAS TRIATMA MULYA - Elizabeth Ni Putu Novitasari; Gde Herry Sugiarto Asana; Made Christin Dwitrayani (Journal Research of Accounting, 2022)
The level of intelligence and good learning behavior is very important to the level of understanding of accounting. This study aims to examine the effect of the level of intelligence and learning behavior on the level of accounting understanding of students in the accounting study program at Triatma Mulya University. This study uses primary data, where data collection is carried out using questionnaires distributed by researchers to respondents who have predetermined criteria. The sample was carried out by purposive sampling method. The number of respondents used in this study were 41 people. The research method used is quantitative research and for data analysis using multiple linear regression analysis with the help of SPSS (Statistical Product and Service Solutions). The results of this study state that the level of intelligence and learning behavior has a positive effect on the level of accounting understanding.